Forensic psychiatry evaluation of criminal law cases at a university hospital in Eastern Turkey - Ersolak, Cüneyt (The journal of forensic psychiatry & psychology, 2023)
This study aimed to determine the epidemiological distribution of the cases referred to the forensic psychiatric assessments according to the reasons for their referral. The medical files of 214 cases referred to the Forensic-Psychiatry Outpatient-Clinic and forensic reports within the scope of criminal law were reviewed retrospectively. 76% of cases were ‘suspected perpetrators’ who were sent for the purpose of determining criminal responsibility, 9.3% were ‘’mentally disordered victims’, 14% were sent to determine ‘victim developing a mental disorder(MD)’. In our study, it was determined that the majority of the suspected perpetrators were male and in the 20–39 age group. Marriage rates were high in both suspected perpetrator groups with(42.2%) or without(39.9%) of MD. The most common diagnosis of suspected perpetrators was schizophrenia/psychosis. Regarding the group sent as perpetrators, it was found that the rate of intellectual disability(ID) has a high rate of 20.2% among all cases, and the diagnoses of substance use disorder(SUD) and personality disorder(PD)were low. Full criminal responsibility was significantly correlated with age, PD, SUD, and pre-criminal substance use. Logistic regression analysis was determined gender and education can predict the perpetration or victimization of individuals with MD. Our findings show that protective-preventive practices specific to risk groups should be developed for the sociodemographic and clinical differences we detected in the Turkish forensic psychiatry sample. In the process of evaluating whether there is a medical problem in the marriage of patients with schizophrenia, possible harm to the spouse and children of the patient should be considered. We are of the opinion that all MD should be evaluated from the perspective of the implementation of preventive security measures, the focus of which is the state of dangerousness.